Manajemen Pembiayaan Peningkatan Kualitas Kinerja Tenaga Kependidikan Sekolah Dasar Negeri - Wahyuni, Amalia Desy (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Educational finance management plays a strategic role in enhancing the performance quality of educational personnel. As an integral part of the education system, educational personnel require adequate financial support to improve their competencies, welfare, and work productivity. This study aims to examine the concept of financial management in the context of improving the quality of educational personnel. The research method employed is a literature review supported by field-based research, analyzing various academic sources related to educational finance management, budget management strategies, and their impact on the performance of educational personnel at UPTD SD Negeri Lombang Dajah 2. The findings indicate that the effectiveness of financing is highly dependent on performance-based planning, the optimization of resources, and transparent and accountable evaluation. Furthermore, the main challenges in financial management include limited budgets, inefficient fund distribution, and the lack of needs-based evaluation for educational personnel. Therefore, a more structured and competency-oriented financial policy is necessary. The implications of this study are expected to serve as a reference for policymakers in designing sustainable and effective financing strategies to support the development of educational personnel within the education system.